Cochlear implant in far advanced otosclerosis. Performance complications-long term results - Curet, Carlos Augusto (2013)
Fil: Curet, Carlos Augusto. Universidad Nacional de Córdoba. Facultad de Ciencias Médicas. Unidad Hospitalaria San Roque. Cátedra II de Otorrinolaringología; Argentina.